Principle and control strategy of pulse width modulation rectifier for hydraulic power generation system. (May 2019) - Wang, Kunlin; Sheng, Songwei; Zhang, Yaqun; Ye, Yin; Jiang, Jiaqiang; Lin, Hongjun; Huang, Zhenxin; Wang, Zhenpeng; You, Yage
Abstract: According to the characteristics of the hydraulic power generation system (HPGS), HPGS can be directly fed into a DC nano grid through using an uncontrolled rectifier. However, determined only by the DC voltage, the motor speed of the HPGS is a constant rather than an optimal speed, whose curve is unknown yet during the whole power generation process. In order to realize the control of the HPGS's motor speed and reduce the armature current harmonics, a pulse width modulation (PWM) rectifier topology is introduced to replace the uncontrolled rectifier. First, the principle of the PWM rectifier is studied. Second, a control structure of this PWM rectifier is established, including a current decoupling control in the inner loop and a speed feedback control in the outer loop. After this, a maximum efficiency converting control strategy is adopted. Based on the above, the simulation model of the PWM rectifier which was fed into DC nano grid was established and a series of experiments were carried out. The experimental results show that the armature current waveform is sine wave and its rectification is flexible. Furthermore, the maximum efficiency converting control strategy is realized with HPGS's always working at the optimal speed curve. Highlights: HPGS is separated from hydraulic energy converting system of WEC. HPGS feeds into DC nano grid. The mathematical model of PWM rectifier for HPGS is established. The maximum efficiency converting control strategy for HPGS is proposed. An optimal speed curve of HPGS is concluded from speed experiments.